High efficiency bifacial n-PERT cells with co-plated Ni/Ag contacts for multi-wire interconnection. (September 2017) - Cornagliotti, Emanuele; Tous, Loic; Russell, Richard; Uruena, Angel; Choulat, Patrick; van der Heide, Arvid; Aleman, Monica; Duerinckx, Filip; Voroshazi, Estzer; Szlufcik, Jozef
Abstract: In this paper we present bifacial n-type PERT cells (n-PERT+) with ultra-thin (< 3 μm) and narrow (< 20 μm) Ni/Ag plated contacts on both the n + and p + side of the cell. This cell architecture is designed for multi-wire interconnection and has the potential to deliver low cost of ownership at module level (< 0.30 /Wp ), as it can profit from bifacial gain, a low cost metallization ( 0.07 /cell) and reduced shadowing and recombination losses. A self-aligned, fully plated metallization sequence, able to form Ni/Ag electrodes simultaneously on both polarities of the cell with a low specific contact resistance, is demonstrated. We benchmark this novel process to a seed-and-plate sequence where the plating seed is obtained by physical vapor deposition (PVD) of Ni and we show comparable efficiency results. Efficiencies of up to 22.8% for cells featuring this fully plated Ni/Ag metallization sequence have been obtained (Cz, 239 cm 2, Grid TOUCH measurement). We also report 1-cell laminates assembled using multi-wire foils reaching maximum power of about 5 W (256 cm 2 aperture area), which shows that the proposed metallization sequence is well suited for integration with such interconnection technology, despite small finger section and the absence of a highly conductive Cu inter-layer. The 1-cell laminates also exhibit less than 4% power degradation after 400 thermal cycles (-40 ºC to +85 ºC).